The Role of Education in the Formation of Tax Ethics in Azerbaijan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper discusses the importance of tax ethics, as well as the impact of education on it. The impact of tax-oriented education on tax ethics was determined in the case of Azerbaijan. For this purpose, it was applied a questionnaire survey to 250 students studied at the Academy of Public Administration under the President of the Republic of Azerbaijan between 2017 and 2019 years. The collected data were analyzed descriptively, and the hypothesis was tested using the Paired Samples Test. Cronbach's Alpha conducted to verify the validity of the research. Analyzes and tests were carried out electronically using the SPSS 16.0 software. As a result of empirical research, it turned out that the attitude towards taxation was higher after passing tax classes.